A scalable and format-compliant encryption scheme for H.264/SVC bitstreams - WEI, Zhuo (Institutional Knowledge at Singapore Management University, 2012)
SVC (Scalable Video Coding) is designed to adapt to heterogeneous networks and various terminal devices. This paper presents an encryption scheme for SVC bitstreams which retains the valuable scalability properties of SVC. To this end, we explore PACSI (Payload Content Scalability Information) and RTP (Real-time Transport Protocol) payload format such that encrypted bitstreams are SVC format-compliant. Specifically, the proposed scheme processes the base layer and enhancement layers in different ways. For the base layer, the scheme encrypts VCL (video coding layer) NALU (Network Abstract Layer Unit) into either SEI (Supplement Enhancement Information) NALU or PACSI NALU. For an enhancement layer, the scheme replaces a coded slice in scalable extension NALU with an encryption of PACSI NALU. Thus, the proposed encryption scheme preserves SVC scalability and format-compliance. It produces encrypted bitstreams which have the original SVC structure without emulation markers or illegal codewords for any standard decoder. The analysis and experiments indicate that our algorithm is cost-effective and secure against chosen plaintext attack.